Calving pattern on captive sambar deer (Cervus unicolor) in East Kalimantan - GONO SEMIADI; I.G. MADE JAYA ADHI; ANDI TRASODIHARTO (Biodiversitas Journal of Biological Diversity, 2005)
Sambar deer (Cervus unicolor) is the biggest of tropical deer with its distribution in Indonesia limited to Kalimantan and Sumatera islands and neighboring islands near Sumatera. Several countries such as Malaysia and Thailand have been developing their tropical deer farming, whereas in Indonesia they are still in its infancy, as captive breeding. The knowledge on the biology of reproduction from tropical deer is still limited, particularly those under their natural habitat. An evaluation on the reproduction profiles of captive sambar deer were conducted by analyzing log book of the captive breeding in East Kalimantan. The results indicated that conception rates was very low, only 48,8% (SD=16.24; n=10 years) with peak calving time between June and July and mean calving date was on 4 July (SD=10.4 days; n=109 fawns). Calving interval was 388,2 days (SD=82.45; n=33 fawns), with natural nursing lasted for 148 days. Young hind gave birth for the first time at the age of 693.8 days (SD=89.40; n=4 hinds), giving a time estimate of first mating at the age of 453 days.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Cervus unicolor, sambar deer, calving pattern, captivity, East Kalimantan.